Analyzing the implementation of heutagogical approach: A case study on writing early childhood education-themed theses in the non-formal education program at the Universitas Negeri Surabaya - Rosyanafi, Rofik; Lestari, GD; Yusuf, A; Nugroho, R; Yulianti, E (Universitas Nahdlatul Ulama Surabaya, 2023)
This study aims to analyze the implementation of heutagogical approach in writing early childhoodeducation-themed theses in the non-formal education program at the Universitas Negeri Surabaya. Thestudy uses a case study method to collect data through observation, interviews, and document analysis. Theparticipants of this study are students who are currently writing their theses in the non-formal educationprogram. The results of this study show that implementing a heutagogical approach in writing earlychildhood education-themed theses can improve students’ critical thinking, creativity, and self-directedlearning skills. The findings of this study can be used as a reference for educators and researchers interestedin implementing heutagogical approach in non-formal education programs.